Development of a Tailored Behavioral Weight Loss Program for Veterans With PTSD (MOVE!+UP): A Mixed-Methods Uncontrolled Iterative Pilot Study. Issue 6 (July 2020) - Hoerster, Katherine D.; Tanksley, Lamont; Simpson, Tracy; Saelens, Brian E.; Unützer, Jürgen; Black, Marissa; Greene, Preston; Sulayman, Nadiyah; Reiber, Gayle; Nelson, Karin
Purpose: Veterans with post-traumatic stress disorder (PTSD) lose less weight in the Veterans Affairs (VA) weight management program (MOVE!), so we developed MOVE!+UP. Design: Single-arm pre–post pilot to iteratively develop MOVE!+UP (2015-2018). Setting: Veterans Affairs Medical Center. Participants: Overweight Veterans with PTSD (5 cohorts of n = 5-11 [N = 44]; n = 39 received ≥1 MOVE+UP session, with cohorts 1-4 [n = 31] = "Development" and cohort 5 [n = 8] = "Final" MOVE!+UP). Intervention: MOVE!+UP weight management for Veterans with PTSD modified after each cohort. Final MOVE!+UP was coled by a licensed clinical psychologist and Veteran peer counselor in 16 two-hour in-person group sessions and 2 individual dietician visits. Sessions included general weight loss support (eg, behavioral monitoring with facilitator feedback, weekly weighing), cognitive-behavioral skills to address PTSD-specific barriers, and a 30-minute walk to a nearby park. Measures: To inform post-cohort modifications, we assessed weight, PTSD, and treatment targets (eg, physical activity, diet), and conducted qualitative interviews. Analysis: Baseline to 16-week paired t tests and template analysis. Results: Development cohorts suggested improvements (eg, additional sessions and weight loss information, professional involvement) and did not lose weight (mean [ M ] = 1.8 lbs (standard deviation [SD] = 8.2); P = .29. Conversely, the final cohort reported high satisfaction and showed meaningful weight ( M = −14 pounds [SD = 3.7] and 71% lost ≥5% baseline weight) and PTSD ( M = −17.9 [SD = 12.2]) improvements, P < .05. Conclusions: The comprehensive, 16-week, in-person, cofacilitated Final MOVE!+UP was acceptable and may improve the health of people with PTSD. Iterative development likely produced a patient-centered intervention, needing further testing.